Intestinal parasitism and risk factors of enteroparasites in schools of the urban zone canton Jipijapa, Ecuador - Murillo-Zavala, Anita María; Rodríguez de Rivero, Zulbey Chiquinquirá; Bracho-Mora, Angela María (Kasmera, 2020)
Enteroparasitosis has global relevance predominantly in underdeveloped countries. The objective of the study was to determine the prevalence of intestinal parasites and risk factors in 340 schoolchildren from the Jipijapa canton. The species were: Enterobius vermicularis, Blastocystis sp. and Endolimax nana and risk factors found agreed with the low prevalence of parasitic species